Tennessee Williams’s post-pastoral Southern gardens in text and on the movie screen - Taïna Tuhkunen (Transatlantica)
This study explores the representation of the American South in the film adaptations of five plays by the Mississippi-born playwright, Tennessee Williams: A Streetcar Named Desire (Elia Kazan, 1951), Baby Doll (Elia Kazan, 1956), Cat on a Hot Tin Roof (Richard Brooks, 1958), Suddenly Last Summer (Joseph L. Mankiewicz, 1959) and The Night of the Iguana (John Huston, 1964). The article focuses on the disrespectful representations of the paradigmatic Southern garden which remains dynamic while maintaining some of its classic or biblical features. By relying on the conception of the pastoral garden as theorized by Leo Marx in The Machine in the Garden (1964), the author pays specific attention to the way mid-xxth century cinema kept recreating Williams’s Southern gardens as a corrupted and dehumanized space pierced through by disquieting shrieks.